Geometry and expression enhance enrichment of functional yeast-displayed ligands via cell panning - Stern, Lawrence A. (Biotechnol Bioeng, 2016)
Yeast surface display has proven to be an effective tool in the discovery and evolution of ligands with new or improved binding activity. Selections for binding activity are generally carried out using immobilized or fluorescently labeled soluble domains of target molecules such as recombinant ectodomain fragments. While this method typically provides ligands with high affinity and specificity for the soluble molecular target, translation to binding true membrane-bound cellular target is commonly problematic. Direct selections against mammalian cell surfaces can be carried out either exclusively or in combination with soluble target-based selections to further direct towards ligands for genuine cellular target. Using a series of fibronectin domain, affibody, and Gp2 ligands and human cell lines expressing a range of their targets, epidermal growth factor receptor and carcinoembryonic antigen, this study quantitatively identifies the elements that dictate ligand enrichment and yield. Most notably, extended flexible linkers between ligand and yeast enhances enrichment ratios from 1.4±0.8 to 62±57 for a low-affinity (>600 nM) binder on cells with high target expression and from 14±13 to 74±25 for a high-affinity binder (2 nM) on cells with medium valency. Inversion of the yeast display fusion from C-terminal display to N-terminal display still enables enrichment albeit with 40% to 97% reduced efficacy. Collectively, this study further enlightens the conditions – while highlighting new approaches – that yield successful enrichment of yeast-displayed binding ligands via panning on mammalian cells.